The Relationship Between Young Pregnant Women and the Incidence of Anemia at Ir. Soekarno Regional General Hospital Morotai Island - Nuning Sulis Taba; Anik Purwati (Lembaga Pengembangan Kinerja Dosen, 2025)
Red blood cells are essential for carrying oxygen and vital nutrients needed for the growth of the fetus, therefore anemia during pregnancy is a complex issue. It is vital for all expectant mothers to fulfill their iron needs because maternal anemia during pregnancy can result in adverse consequences for the child, such as premature birth and low birth weight. The chance of a woman developing anemia increases as she ages during pregnancy. Bleeding is a direct result of the anemia experienced during labor in 17.24% of cases. The purpose of this study was to determine the connection between the incidence of anemia and young pregnant women in Ir. Soekarno Hospital on Morotai Island. The study used an analytical survey with a cross-sectional approach, which is useful for finding relationships between two or more variables. The whole sampling technique, which included 40 participants in all, was used. A checklist was used as the study's instrument. Chi-Square analysis was used to analyze the collected data using SPSS software. The chi-square statistical analysis produced a P-value (asymp. The p-value (2-tailed) is 0.002, which is less than the 0.05 significance level. This indicates a relationship between the start of anemia and young pregnant women. Thus, it is possible to infer a link between the incidence of anemia and young pregnant women, leading to the rejection of H0 and the endorsement of H1.